Influence of Eastern, Central and Mix El Niño on the variability of rainfall in southeastern South America - Goudard, Gabriela; Limberger, Leila; Carpenedo, Camila Bertoletti (Frontiers in Earth Science, 2024)
El Niño/Southern Oscillation (ENSO) plays a very important role in modulating rainfall variability in South America. Although the effects of conventional ENSO are well known, there are significant variations in rainfall patterns when sea surface temperature anomalies manifest over the different regions along the equatorial Pacific, namely, Niño 3 (East), Niño 3 and Niño 4 (Mix), and Niño 4 (Central) ENSO. This work aims to analyze the variability of precipitation in southeastern South America associated with different types of El Niño (EN). For this, composite analyzes of precipitation, winds at low and high levels, vertical velocity and geopotential height were carried out. The results indicate that the rainfall pattern associated with Eastern Pacific (EP) El Niño shows the classic features expected from EN described in previous literature, i.e., a stronger and well-defined positive precipitation anomaly over southeast South America, while Central Pacific (CP) El Niño shows weaker and even an opposite sign over the region. Mix (MX) El Niño events present a spatial pattern of precipitation anomalies similar to EP El Niño events, but with lower intensity in the study area. The heterogeneity of EN-related precipitation effects results from a change in large-scale atmospheric circulation patterns: the Walker cell in the tropics, the Rossby waves in the extratropics, and the circulation of low and high-level jet streams. EP El Niño events feature a configuration similar to the South American Low-Level Jet, the strengthening of the subtropical jet, better structured Rossby waves and the Pacific-South America pattern. These characteristics are observed in MX El Niños, but in a weaker way compared to EP El Niños. CP El Niño events, on the other hand, present a weakening and spatial displacement of the aforementioned conditions, which is reflected in negative precipitation anomalies in most seasons. Thus, more significant rainfall variations are noted between the EP El Niños and CP El Niños, with a predominance of positive and negative rainfall anomalies in the study area, respectively.